2010
DOI: 10.1177/0016986210377927
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Probability of Identification for Gifted Programs for Students in Georgia Elementary Schools: A Multilevel Path Analysis Study

Abstract: This study focused on the analysis of a large-scale data set (N = 326,352) collected by the Georgia Department of Education using multilevel path analysis to model the probability that a student would be identified for participation in a gifted program. The model examined individual-and school-level factors that influence the probability that an individual would be identified. The probability of being identified as gifted depended strongly on student race and socioeconomic status and varied strongly across sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 47 publications
5
52
0
Order By: Relevance
“…Many standardized tests used for gifted identification are inappropriate or suboptimal for use with children from culturally diverse groups, due to cultural/language bias, differential predictive validity for Black students, and stereotype threat and anxiety that are invoked from the tests among Black students (Ford and Whiting 2010;Matthews and Kirsch 2011). Moreover, school teachers often serve as gate-keepers to gifted programs given reliance on teacher recommendations (Ford et al 2008;McBee 2010). Subjective selection practices are often influenced by teachers' negative attitudes and expectations toward Black students, and poorer teacher-student relationships with Black males in particular (Henfield et al 2008b).…”
Section: Black Males In Gifted Programsmentioning
confidence: 99%
“…Many standardized tests used for gifted identification are inappropriate or suboptimal for use with children from culturally diverse groups, due to cultural/language bias, differential predictive validity for Black students, and stereotype threat and anxiety that are invoked from the tests among Black students (Ford and Whiting 2010;Matthews and Kirsch 2011). Moreover, school teachers often serve as gate-keepers to gifted programs given reliance on teacher recommendations (Ford et al 2008;McBee 2010). Subjective selection practices are often influenced by teachers' negative attitudes and expectations toward Black students, and poorer teacher-student relationships with Black males in particular (Henfield et al 2008b).…”
Section: Black Males In Gifted Programsmentioning
confidence: 99%
“…The Malaysian National Gifted Center -also known as PERMATApintar™ -used two standardized tests to measure the following group of abilities: intellectual, creativity, socio-affective and sensorimotor. Research have shown that standardized tests are useful especially in identifying students with exceptional academic potential who are underrepresented in gifted and talented program (Peters & Gentry, 2010;Ford, 1998;McBee, 2010;Pfeiffer & Jarosewich, 2007). It provides consistency in the selection process.…”
Section: Identification Program -The Malaysian Experiencementioning
confidence: 99%
“…Although changes in IQ scores over time have drawn attention in general and special education settings (Flynn, 2000;Kanaya et al, 2003), there appears to have been little consideration of how these changes might influence gifted identification rates. Despite a growing recognition that giftedness may involve additional factors beyond intelligence test scores (Callahan, 2005;McBee, 2010;Steiner & Carr, 2003;Sternberg, 2007) and a growing awareness of potential sources of bias in the gifted referral process (McBee, 2010), these test scores remain a central factor in determining who is eligible to receive gifted education services in schools. In the present article, we use the broader term aptitude testing to refer to standardized intelligence testing in general, while we use the more specific term IQ to refer to specific measures within this genre.…”
Section: Aptitude (Iq) Testing In Gifted Identificationmentioning
confidence: 99%